Foraging ecologies of giraffe (Giraffa camelopardalis reticulata) and camels (Camelus dromedarius) in northern Kenya: effects of habitat structure and possibilities for competition? - O'Connor, David A.; Butt, Bilal; Foufopoulos, Johannes B. (African Journal of Ecology, 2015)
The foraging ecologies of reticulated giraffe (Giraffa camelopardalis reticulata) and domestic camels (Camelus dromedarius) were examined in the Laikipia District of Kenya, where these species have recently become sympatric. Camels increased popularity in the region has lead to concerns about their environmental impacts and possible competition with wild giraffe for resources. We gathered foraging data on both species using 2‐min group scans that recorded feeding heights and plant food preferences. Transects sampled the vegetation in areas where foraging observations were recorded. Giraffe females feed at lower elevations than males, while female camels feed below both sexes of giraffe. There was very little observed overlap in food preferences between the species. However, habitat type has an effect on foraging ecologies of both giraffe sexes, but habitat did not influence camel foraging. Camel herder husbandry techniques also influence camel foraging dynamics. These findings have important implications in achieving the twin objectives of wildlife conservation and pastoralist livestock production in northern Kenya.RésuméL'écologie alimentaire de la girafe réticulée (Giraffa camelopardalis reticulata) et celle du dromadaire (Camelus dromedarius) ont été étudiées dans le District de Laikipia, au Kenya, où ces espèces sont récemment devenues sympatriques. La popularité croissante des dromadaires dans la région a suscité des inquiétudes au sujet des impacts sur l'environnement et d'une éventuelle compétition pour les ressources avec les girafes sauvages. Nous avons récolté des données sur l'alimentation des deux espèces au moyen de scan de groupe de deux minutes, qui enregistraient la hauteur à laquelle les animaux mangeaient et les plantes préférées. Des transects ont permis de récolter des échantillons de végétation dans les zones où les observations alimentaires ont été faites. Les girafes femelles se nourrissent plus bas que les mâles et les dromadaires femelles se nourrissent plus bas que les girafes des deux ...